Involvement of collagen-binding heat shock protein 47 in scleroderma-associated fibrosis. Issue 8 (20th June 2015) - Chu, Haiyan; Wu, Ting; Wu, Wenyu; Tu, Wenzhen; Jiang, Shuai; Chen, Sidi; Ma, Yanyun; Liu, Qingmei; Zhou, Xiaodong; Jin, Li; Wang, Jiucun
Abstract: Uncontrolled fibrosis of skin and internal organs is the main characteristic of scleroderma, and collagen is a major extracellular matrix protein that deposits in the fibrotic organs. As the chaperone of collagen, heat shock protein 47 (HSP47) is closely related with the development of fibrosis. To explore the potential function of HSP47 in the pathogenesis of scleroderma, the clinical, in vivo and in vitro studies were performed. In clinical, the increased mRNA level of HSP47 was observed in the skin fibroblasts and PBMC from scleroderma patients, and the enhanced protein level of HSP47 was also detected in the skin biopsy and plasma of the above patients. Unexpectedly, the enhanced levels of HSP47 were positively correlated with the presence of anti-centromere antibody in scleroderma patients. Moreover, a high expression of HSP47 was found in the skin lesion of BLM-induced scleroderma mouse model. Further in vitro studies demonstrated that HSP47 knockdown could block the intracellular and extracellular collagen over-productions induced by exogenous TGF-β. Therefore, the results in this study provide direct evidence that HSP47 is involved in the pathogenesis of scleroderma. The high expression of HSP47 can be detected in the circulatory system of scleroderma patients, indicating that HSP47 may become a pathological marker to assess the progression of scleroderma, and also explain the systemic fibrosis of scleroderma. Meanwhile, collagen over-expression is blocked by HSP47 knockdown, suggesting the possibility that HSP47 can be a potential therapeutic target for scleroderma.